Hidden Markov Model for Time Series Prediction - Hanif, Muhammad; Sami, Faiza; Hyder, Mehvish; Ch, Muhammad Iqbal (Journal of Asian Scientific Research, 2017)
The Hidden Markov Model (HMM) is a powerful statistical tool for modeling generative sequences that can be characterized by an underlying process generating an observable sequence. Hidden Markov Model is one of the most basic and extensively used statistical tools for modeling the discrete time series. In this paper using transition probabilities and emission probabilities different algorithm are computed and modeled the series and the algorithms to solve the problems related to the hidden markov model are presented. Hidden markov models face some problems like learning about the model, evaluation process and estimate of parameters included in the model. The solution to these problems as forward-backward, Viterbi, and Baum Welch algorithm are discussed respectively and also useful for computation. A new hidden markov model is developed and estimates its parameters and also discussed the state space model.